DISSENTING OPINION ON SOCIAL AID POLITICIZATION AND STATE APPARATUS MOBILITY: IMPLICATIONS FOR THE QUALITY OF DEMOCRACY - Muhammad Shohibul Ihzar; Hardianti Alimuddin (Jurnal Al Tasyri'iyyah, 2024)
ABSTRACT Resolving disputes The dispute over the results of the general election has resulted in dissenting opinions or differences of opinion expressed by three judges, namely Saldi Isra, Enni Nurbaningsih, and Arief Hidayat. The three judges were of the opinion that there had indeed been fraud in the 2024 presidential election, especially regarding the applicant's argument regarding Social Assistance, which was caused by the distribution of social assistance by President Joko Widodo at the wrong time and the mobility of state officials. This research can provide deep insight into how legal institutions play an important role in strengthening the quality of democracy in a country. This research is library research with a normative juridical approach. Research data sources involve references from relevant journals, regulations and online media. The findings of this research are analyzing the legal basis that supports the dissenting opinion of constitutional court judges, and the implications of dissenting opinions on the quality of democracy. The conclusion of this research is that the distribution of social assistance during the campaign period and the involvement of state officials in general elections are considered violations, this is based on Law Number 7 of 2017 and General Election Commission Regulation Number 23 of 2018. In addition, the dissenting opinion of the Constitutional Court judge in the 2024 case, it has implications for the quality of democracy, namely increasing the quality of supervision, increasing public awareness, and increasing transparency of the general election process. Keywords: Dissenting Opinion; Politicization Of Social Assistance; Mobility Of State Apparatus; Demokracy